2017
DOI: 10.1186/s40104-017-0188-y
|View full text |Cite
|
Sign up to set email alerts
|

Impact of dietary l-arginine supply during early gestation on myofiber development in newborn pigs exposed to intra-uterine crowding

Abstract: BackgroundIntra-uterine crowding (IUC) observed in hyperprolific sows impairs myofiber hyperplasia and overall fetal growth. Arginine supplementation (ARG) in gestation diets has been shown to positively affect litter and muscle development. The study objective was to assess whether the effect of ARG on offspring characteristics, with special emphasis on myofiber hyperplasia, differs under IUC conditions from these responses, because in that situation growth retardation is particularly prevalent due to reduced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 46 publications
(59 reference statements)
0
16
1
Order By: Relevance
“…The decreased values for within‐litter standard deviation and within‐litter coefficient of variation of piglet birthweights highlight the potential of L‐arginine supplementation to improve litter uniformity and lower the incidence of piglets with low viability (Madsen, Pardo, Kreuzer, & Bee, ; Palencia et al, ; Shi et al, ). Quesnel et al () observed a decreased coefficient of variation and improved uniformity in piglet birthweights after L‐arginine supplementation during the final third of gestation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The decreased values for within‐litter standard deviation and within‐litter coefficient of variation of piglet birthweights highlight the potential of L‐arginine supplementation to improve litter uniformity and lower the incidence of piglets with low viability (Madsen, Pardo, Kreuzer, & Bee, ; Palencia et al, ; Shi et al, ). Quesnel et al () observed a decreased coefficient of variation and improved uniformity in piglet birthweights after L‐arginine supplementation during the final third of gestation.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased numbers of low-weight piglets are of great interest because low-birthweight piglets have significantly lower daily weight gains until weaning and during subsequent stages than do high-birthweight piglets (Beaulieu, Aalhus, Williams, & Patience, 2010;Fix et al, 2010;Lanferdini et al, 2018), who also show higher mortality rates (Hales, Moustsen, Nielsen, & Hansen, 2014) and need more time to reach market weight (Beaulieu et al, 2010;López-Vergé et al, 2018). Dietary supplementation with L-arginine may help increase the nitric oxide content in endothelial cells that line blood vessels, thus increasing the blood flow, causing vasodilatation and decreasing weight variations and the incidence of low-weight piglets (Campos et al, 2008;Madsen et al, 2017;Mateo, Wu, Moon, Carroll, & Kim, 2008). Genetic improvement may also increase weight-at-birth uniformity and can be performed indirectly by selecting for survival, birthweight and uterine capacity (Kapell, Ashworth, Knap, & Roehe, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Improved trophectoderm cell proliferation and subsequent placental development during the establishment of the fetal-maternal interface is considered a mechanism through which Arg may contribute to increased litter size and birth weight. However, the effects of Arg supplementation on litter size is inconsistent (Bérard and Bee, 2010;Quesnel et al, 2014;Garbossa et al, 2015;Dallanora et al, 2017;Madsen et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…The nutritional requirement of Arg is highly dependent on environmental and physiological conditions. Therefore, stressors such as microbial change, heat stress, and sepsis dramatically increase the Arg requirements [10][11][12].…”
Section: Introductionsmentioning
confidence: 99%